SURFACE ZETA POTENTIAL AS A BIOMARKER FOR MONITORING HUMAN RED BLOOD CELLS - Eberl, Brandon (Wake Forest University, 2026)
Red blood cells (RBCs) are the most abundant cell in the human body. RBCs play a critical role maintaining physiologic homeostasis through oxygen and carbon dioxide exchange. Negative surface charge is an important property of RBCs that prevents them from clumping and adhering to vessels or other cells via the repulsive, negative force. During normal circulation and in disease processes (e.g., cardiovascular disease and RBC-related diseases) RBCs can be damaged and membrane surface charge can be impacted. This damage can be induced by oxidative stress (OS) as well as exposure to mechanical shear stress produced by physiologic circulation and mechanical circulatory support devices. Conventionally, erythrocyte sedimentation rate (ESR) has been used to quantify surface charge-induced RBC aggregation, by measuring the time required for RBCs to settle at the bottom of a glass tube. However, ESR cannot directly measure the electrostatic forces responsible for causing RBC aggregation.
Keywords: cardiology; cardiopulmonary bypass; electrophoresis; extracorporeal membrane oxygenation; red blood cell; surface zeta potential